2017
DOI: 10.1080/17470218.2016.1195852
|View full text |Cite
|
Sign up to set email alerts
|

Shared Structuring Resources across Domains: Double Task Effects from Linguistic Processing on the Structural Integration of Pitch Sequences

Abstract: 1Many studies have reported evidence suggesting that resources involved in linguistic structural 2 processing might be domain-general by demonstrating interference from simultaneously presented non-3 linguistic stimuli on the processing of sentences (Slevc, Rosenberg, & Patel, 2009). However, the 4 complexity of the analyzed linguistic processes often precludes the interpretation of such interference as 5 being based on structural -rather than more general -processing resources (Perruchet & Poulin-6 Charronnat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…For example, the cerebellum has been implicated in mathematical cognition as well as in grammatical processes and music perception (Doya, 1999; Riva and Giorgi, 2000; Janata and Grafton, 2003; Wartenburger et al, 2003; Murdoch, 2010; Pliatsikas et al, 2014; Dehaene et al, 2015). We suggest that the brain network responsible for patterning, sequencing, and chunking can mediate cross-representational interaction effects for the concepts that rely heavily on hierarchical organization of linear sequences such as grammatical, arithmetic, and musical phrases (Scheepers et al, 2011; Van de Cavey and Hartsuiker, 2016; Van de Cavey et al, 2016). …”
Section: Representational Overlap: Interactions Between Partially Relmentioning
confidence: 97%
“…For example, the cerebellum has been implicated in mathematical cognition as well as in grammatical processes and music perception (Doya, 1999; Riva and Giorgi, 2000; Janata and Grafton, 2003; Wartenburger et al, 2003; Murdoch, 2010; Pliatsikas et al, 2014; Dehaene et al, 2015). We suggest that the brain network responsible for patterning, sequencing, and chunking can mediate cross-representational interaction effects for the concepts that rely heavily on hierarchical organization of linear sequences such as grammatical, arithmetic, and musical phrases (Scheepers et al, 2011; Van de Cavey and Hartsuiker, 2016; Van de Cavey et al, 2016). …”
Section: Representational Overlap: Interactions Between Partially Relmentioning
confidence: 97%
“…Both behavioural Fiveash et al, 2018;Fiveash & Pammer, 2014;Hoch et al, 2011;Slevc et al, 2009) and neurophysiological (Carrus et al, 2013;Koelsch, Gunter, et al, 2005;Steinbeis & Koelsch, 2008) studies have shown interference between syntactic integration processing for language and music, which typically was not shown with semantic errors in language or with timbral or loudness manipulations in music. Note that the syntax-specificity of these shared mechanisms is still debated, with links to other shared resources including syntactic working memory (Fiveash & Pammer, 2014;Kljajevic, 2010), structural reintegration (Van de Cavey et al, 2017), cognitive control (Slevc & Okada, 2014), and more recently, hierarchical control (Asano et al, 2015;. See also Perruchet and Poulin-Charronnat (2013) and discussion in Hoch et al (2011) for links with semantics and the importance of considering potential differences in the strength of the used syntactic/semantic violation.…”
Section: Shared Cognitive and Neural Mechanismsmentioning
confidence: 99%
“…To further investigate whether interference effects were specifically related to shared syntactic processing resources, Van de Cavey, Severens, and Hartsuiker (2017) 28 contrasted syntactic garden path sentences with syntactic anomalies while participants were concurrently listening to pitch sequences that contained “clusters” of related notes. Cluster shifts (moving from one group of related notes to another group of related notes) were introduced either concurrently or non-concurrently with the unexpected sentence element.…”
Section: Introductionmentioning
confidence: 99%